(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: تحاول الرواية الجزائري تأثيث كينونتها ضمن الفضاء الإبداعي العربي، راسمة آفاق المتخيل إنتاجا وقراءة. ولما كان الفضاء الصحراوي الجزائري زاخرا بتيماته وعمق أصالته وتنوع ثقافاته، جعل منه مبعثا ومثارا احتوته الرواية الصحراوية الجزائرية منها: مملكة الزيوان للحاج أحمد صديق. -تتمثل شعرية الروائي في استثمار الفضاء وتداوله وأبعاده التاريخية لرسم مملكة الزيوان، يعضده في ذلك آليات السرد الروائي في بنية هذا النص، وتشاكل مقروئيته. فإلى أي مدى أسهمت شعرية الفضاء وأبعادها التداولية في تحليل النص الصحراوي عموما والرواية خصوصا؟ وهل استطاعت أن تلامس أدبية النص في (رواية مملكة الزيوان)؟ وكيف يمكن قراءة تعدد الخطابات وتقاطع الفضاءات داخل الرواية وأثره في استجلاء أدبية هذه الرواية؟ كلمات دالة: شعرية؛ فضاء؛ سرد؛ مملكة الزيوان. Abstract: The Algerian novel tries to furnishitsbeingwithin the Arabcreativespace, drawing the horizons of the imagined in production and reading. When the Algerian desertspacewas full of itstimeliness, the depth of itsoriginality and the diversity of its cultures, it made it a source and an excitementthatcontained the Algerian desertnovel, including: The Kingdom of Ziouan by Hajj Ahmed Siddiq. To whatextentdid the poetry of space and itsdeliberative dimensions contribute to the analysis of the Sahrawitext in general and the novel in particular? And wasshe able to touch the literarytext of (The Kingdom of Ziwannovel)? How isit possible to read the multiplicity of discourses and the intersection of time and place within the novel and itseffect on the literary clarification of thisnovel? Key Words:poetic; Space; Narrative; Kingdom of Ziwan.